Unleashing Potential: How Human and Social Capital Fuel Village Tourism Business Success - I Gde Wedana Arjawa; Putu Ayu Sita Laksmi; Ni Nyoman Suriani (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the influence of human capital and social capital on business performance in tourism villages, focusing on Penglipuran Village in Bali, Indonesia. Tourism villages play a key role in sustainable local economic development, yet their business outcomes often remain suboptimal due to structural and institutional limitations. Using a quantitative approach, this research highlights how intangible assets such as knowledge, skills, trust, and social cohesion drive the success of rural tourism enterprises. Human capital, reflected in education, entrepreneurial experience, and technical competence, enhances innovation, service quality, and adaptive capacity. Social capital, encompassing mutual trust, shared values, and collaborative networks, fosters cooperation and knowledge exchange essential for community-based tourism. Their interaction produces a synergistic effect that strengthens resilience and competitiveness within rural business ecosystems. Data were collected through structured surveys of 155 entrepreneurs and community members, supported by supplementary interviews, and analysed using multiple regression to test the effects of human and social capital on business performance. This study fills a gap in the literature by examining both capitals simultaneously in a rural tourism setting, which has often been overlooked. The findings reveal that both human and social capital significantly improve performance, with social cohesion playing a particularly critical role. The study offers insights for policymakers, tourism stakeholders, and development practitioners by emphasising integrated strategies that support human development and community empowerment. Ultimately, strengthening these capitals is vital for advancing inclusive and sustainable tourism that benefits not only the economy but also the cultural and social fabric of rural communities.